2020
DOI: 10.1007/s00217-020-03618-5
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical characterization of wines produced using indigenous yeasts from cold climate grapes

Abstract: The aim of the study was the physicochemical characterization of wines produced using indigenous yeasts isolated from spontaneously fermented grape musts, obtained from cold climate grapes. Saccharomyces cerevisiae MH020215 and Nakawazaea ishiwadae MG971259 yeast strains were used in this study. The musts obtained from white and red grapes of Johanniter and regent varieties were used as a fermentation raw material. In the produced wines, content of ethyl alcohol, total extract, sugars, free amino nitrogen was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Our studies showed the opposite tendency ( Table 5 ). Our previous research [ 65 ] concerned the physicochemical characterization of wines produced using indigenous yeasts from cold climate grapes. S. cerevisiae strain MH020215 has been shown to produce comparable amounts of isoamyl acetate and slightly lower ethyl acetate in cold climate wines, compared to the results in this article [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our studies showed the opposite tendency ( Table 5 ). Our previous research [ 65 ] concerned the physicochemical characterization of wines produced using indigenous yeasts from cold climate grapes. S. cerevisiae strain MH020215 has been shown to produce comparable amounts of isoamyl acetate and slightly lower ethyl acetate in cold climate wines, compared to the results in this article [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our previous research [ 65 ] concerned the physicochemical characterization of wines produced using indigenous yeasts from cold climate grapes. S. cerevisiae strain MH020215 has been shown to produce comparable amounts of isoamyl acetate and slightly lower ethyl acetate in cold climate wines, compared to the results in this article [ 65 ]. Other esters such as ethyl hexanoate, ethyl butanoate, ethyl pyroracemate, ethyl octanoate and diethyl succinate were identified in slightly lower concentrations in the analysed samples ( Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The apple wine (sample F) pitched with S. cerevisiae SC01 (control) received the lowest scores for appearance, flavor, taste and overall acceptability. A study by Cioch-Skoneczny, Satora, Skoneczny, and Klimczak (2021) revealed that wine samples fermented with S. cerevisiae MH020215 received the highest scores for organoleptic properties, while much lower values were reported for wine pitched with Nakawazaea ishiwadae.…”
Section: Discussionmentioning
confidence: 99%
“…During the last few years, NMR-based metabolomics has been applied to characterize complex food matrices and has been widely used in profiling food samples for quality and authentication assessment ( Rocha & Sheen, 2018 ). Authenticity of alcoholic beverages has been extensively investigated because it is a product that can be easily adulterated due to its signature chemical properties (high alcohol content, low pH) and its availability throughout the world ( Ahmad et al, 2018 , Cioch-Skoneczny et al, 2020 ). In addition to authenticity, traceability has an important role in the quality assurance of alcoholic beverages.…”
Section: Recent Applications Of Nmr-based Metabolomicsmentioning
confidence: 99%